THE INFLUENCE OF FINANCIAL RATIOS TOWARD STOCK PRICE OF PHARMACEUTICAL COMPANIES IN INDONESIA - Afri Yeni Lubis; Purwanto Purwanto (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
The research objectives to examine the influence of current ratio, debt to equity ratio, return on equity, total asset turnover ratio, and earnings per share on stock price with an additional price-earnings ratio as moderating variable of current ratio, debt to equity, and earning per share of pharmaceutical companies listed in Indonesia Stock Exchange. The quantitative research is applied through data from the financial reports among six samples of pharmaceutical companies from 2009-2020 with the analytical tool EViews 10, with other supporting tests such as descriptive statistical analysis, classical assumption, multiple linear regression, and hypothesis testing. The use of multiple linear regression on panel data bolsters to choice of the Fixed Effect Model technique. The results depict a value of adjusted R-square of dependent variables by 64.38%, which CR, DER, TATO, and EPS significantly influence the stock price. Meanwhile, PER does not moderate EPS impact on stock price, yet, moderates CR and DER effect on the stock price.